A New Active Locomotion Capsule Endoscopy under Magnetic Control and Automated Reading Program - Dong Jun Oh; Kwang Seop Kim; Yun Jeong Lim (Korean Society of Gastrointestinal Endoscopy, 2020)
Capsule endoscopy (CE) is the first-line diagnostic modality for detecting small bowel lesions. CE is non-invasive and does not require sedation, but its movements cannot be controlled, it requires a long time for interpretation, and it has lower image quality compared to wired endoscopy. With the rapid advancement of technology, several methods to solve these problems have been developed. This article describes the ongoing developments regarding external CE locomotion using magnetic force, artificial intelligence-based interpretation, and image-enhancing technologies with the CE system.